ChemInform Abstract: Yb14MgSb11 and Ca14MgSb11 — New Mg‐Containing Zintl Compounds and Their Structures, Bonding, and Thermoelectric Properties. Issue 12 (March 2015) - Hu, Yufei; Wang, Jian; Kawamura, Airi; Kovnir, Kirill; Kauzlarich, Susan M.
Abstract The Zintl phases Yb14MgSb11 (I) and Ca14MgSb11 (II) are prepared by annealing mixtures of the elements in the molar ratio Yb(Ca):Mg:Sb of 14:2:11 (Nb tube in evacuated silica tubes, 1275 K for (I) and 1225 K for (II)).